(untitled) (Texas Journal of Medical Science, 2026)
The study evaluated changes in renal functional status in patients with stage 3 chronic kidney disease (CKD) who had previously experienced COVID-19 infection. A total of 131 patients were included in the study: • Group 1 — CKD stage 3 (n=70); • Group 2 — CKD stage 3 + COVID-19 (n=61). For each patient, the lipid profile was evaluated, including: Total cholesterol (TC, mmol/L), Triglycerides (TG, mmol/L), Low-density lipoprotein cholesterol (LDL-C, mmol/L), High-density lipoprotein cholesterol (HDL-C, mmol/L) Laboratory measurements were performed at 1 month and 3 months. Data are presented as mean ± SEM. Statistical analysis was conducted using Student’s t-test or appropriate parametric tests. Significant changes over the 3-month period were indicated with an asterisk (*), p